Acute respiratory distress syndrome associated with severe ulcerative colitis - Sagara, Shiho (The WJG Press and Baishideng, 2010)
Various extraintestinal manifestations including pulmonary abnormalities have been reported in patients with ulcerative colitis. Acute respiratory distress syndrome (ARDS) is a serious and fatal pulmonary manifestation. We have experienced a 67-year-old male patient with ARDS associated with a severe type of ulcerative colitis (UC). Severe dyspnea symptoms occurred during the treatment of UC in a previous hospital and the patient was transferred to our hospital on June 27, 2007. Both blood and sputa cultures for bacteria and fungi were negative. Cytomegalovirus antigenemia was also not detected. From the clinical and radiological [Chest X-ray, computed tomography (CT)] findings, the patient was diagnosed with ARDS on the basis of the definition of ARDS developed by the European-American Consensus Conference on ARDS. Both colonic inflammations and ARDS symptoms of the patient were resistant to any medical treatment including corticosteroids and antibiotics. However, ARDS symptoms were dramatically improved after surgical colectomy. We believe that severe colonic inflammation from UC was closely associated with the onset of ARDS of the patient. Our case report suggests that a severe type of ulcerative colitis might be taken into consideration as one of the predisposing factors of ARDS.